Compatibility of Mycorrhizae and Pineapple-Based Liquid Fertilizer on Local Variety of Shallot for Suppression of Fusarium Wilt Disease: Kecocokan Antara Mikoriza dan Pupuk Organik Cair Berbasis Nanas pada Bawang Merah Varietas Lokal untuk Menekan Penyakit Layu Fusarium - Wafa, Ali; Muwahidi, Amirul; Pradana, Ankardiansyah Pandu; Prastowo, Sigit; Purwandarini, Anggi Arsy (Jurnal Fitopatologi Indonesia, 2024)
A comprehensive approach is needed to control shallots twisted disease (penyakit moler) caused by infection of Fusarium oxysporum. The use of mycorrhiza is known to be quite promising for controlling Fusarium wilt. Many farmers combine biological control agents with plant waste—pineapple peel waste—, but the synergistic effects are not yet clearly known. This research aims to determine the compatibility of liquid fertilizer and mycorrhiza as an effort to develop new techniques in managing Fusiarium twisted disease. The research was arranged using a completely randomized design with 8 treatments and 3 replications. The tests conducted included measuring the percentage of mycorrhizal infectivity and disease severity, bulb production, and biomass of shallot plants. The analysis of the content of pineapple peel-based liquid organic fertilizer (PLOF) showed that it contains 11.14% organic carbon source, 0.14% nitrogen, as well as other macro and micronutrients. The combination of mycorrhiza and PLOF can form a symbiosis with plant roots with a colonization rate of 66.67%. Meanwhile, the combination of the two treatments could not suppress the severity of twisted disease, nor could it increase bulb production and biomass of shallot plants.